Sudden hearing loss: frequency of abnormal findings on contrast-enhanced MR studies. - Fitzgerald, D C; Mark, A S (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Our purpose was to determine the frequency of abnormal findings on contrast-enhanced high-resolution MR imaging studies in patients with sudden hearing loss.METHODS Seventy-eight consecutive patients with sudden hearing loss underwent contrast-enhanced MR imaging of the temporal bone, cerebellopontine angle, and brain. Additional tests included audiologic examination, electrocochleography, fistula tests, and serologic tests for viral agents and autoimmune disorders.RESULTS Probable causes of the sudden hearing loss in these patients included viral or immune-mediated disease, Meniere disease, vascular disorder, syphilis, neoplasm, multiple sclerosis, and perilymphatic fistula. Twenty-four (31%) of the 78 patients were found to have abnormal imaging results early in the course of their work up and treatment.CONCLUSION The prevalence of abnormal findings on contrast-enhanced MR studies is higher than previously reported in patients with sudden hearing loss.